ABCG2 is not able to catalyze glutathione efflux and does not contribute to GSH-dependent collateral sensitivity - Gauthier, Charlotte; Ozvegy-Laczka, Csilla; Szakacs, Gergely; Sarkadi, Balazs; Di Pietro, Attilio (Frontiers in Pharmacology, 2013)
ABCG2 is a key human ATP-Binding Cassette (ABC) transporter mediating cancer cell chemoresistance. In the case of ABCC1, another multidrug transporter, earlier findings documented that certain modulators greatly increase ABCC1-mediated GSH efflux and, upon depletion of intracellular glutathione (GSH), induce “collateral sensitivity” leading to the apoptosis of multidrug resistant cells. Recently, it has been suggested that ABCG2 may mediate an active GSH transport. In order to explore if ABCG2-overexpressing cells may be similarly targeted, we first looked for the effects of ABCG2 expression on cellular GSH levels, and for an ABCG2-dependent GSH transport in HEK293 and MCF7 cells. We found that, while ABCG2 overexpression altered intracellular GSH levels in these transfected or drug-selected cells, ABCG2 inhibitors or transport modulators did not influence GSH efflux. We then performed direct measurements of drug-stimulated ATPase activity and 3H-GSH transport in inside-out membrane vesicles of human ABC transporter-overexpressing Sf9 insect cells. Our results indicate that ABCG2-ATPase is not modulated by GSH and, in contrast to ABCC1, ABCG2 does not catalyze any significant GSH transport. Our data suggest no direct interaction between the ABCG2 transporter and GSH, although a long-term modulation of cellular GSH by ABCG2 cannot be excluded.